Open innovation strategies of smartphone manufacturers: External resources and network positions - Paik, Jiwon; Chang, Hyun Joon (International Journal of Industrial Engineering: Theory, Applications and Practice, 2014)
A smartphone is not only a product with various integrated components but it is also a value added service. As the smartphone ecosystem has evolved in the value chain of the ICT industry, smartphone manufacturers have a need for open innovation such as external resources and collaboration networks. However, most studies on smartphones have focused on product innovation such as functional differentiation, usability, and market penetration rather than innovation networks. The aim of this study is to examine how the open innovation and strategic fit of smartphone manufacturers function in their innovation output and business performance. This research focuses on the relationship between the manufacturers and collaboration partners in the four areas: hardware components, software, content services, and telecommunications. The data of seven smartphone manufacturers from the past 10 years was analyzed.